Pembuatan Karya Seni Kolase dengan Potongan Kertas Origami untuk Meningkatkan Motorik Halus Anak di SD 0310 Simaninggir Desa Sibual-Buali Kecamatan Sosospan - Daulay, Hopman; Nasution, Salwa; Khoiriya, Saibatul; Hasibuan, Annisa; Niswah, Nur; Sahara, Siti Nur (Lembaga Einstein College, 2025)
This comunity service activity was carried out at SD Negeri 0310 Simaninggir to improve children’s fine motor skills by making collages from paper cuttings. This activity is motivated by the children’s still laking fine motor skills including their inability to hold writing tools correctly and their fine motor skill still being hindered when playing. The subjects of this research are class V children of SD Negeri 0310 Simaninggir Sosopan District. Data collection techniques were carried out through observation during the activity and assessment of children’s development was measured using teacher observation sheets with the technique of assessing the results of their work. Thus, it can be concluded that making collages with paper cuttings can improve the fine motor skills of children at SD Negeri 0310 Simaninggir Sosopan District.